Energy Storage and Thermostability of Li3VO4-Coated LiNi0.8Co0.1Mn0.1O2 as Cathode Materials for Lithium Ion Batteries - Song, Liubin; Tang, Fuli; Xiao, Zhongliang; Cao, Zhong; Zhu, Huali (Frontiers in Chemistry, 2018)
The energy storage and thermostability of LiNi0.8Co0.1Mn0.1O2 is affected by temperature. High ambient temperature or irregular heat distribution accelerates the decline of LiNi0.8Co0.1Mn0.1O2 performance, shortens cathode material life. In this work, the nergy storage and thermostability of the Li3VO4-coated LiNi0.8Co0.1Mn0.1O2 cathode material were studied for the first time by electrochemical calorimetry methode at different temperatures and rates. Results show that Li3VO4-coated LiNi0.8Co0.1Mn0.1O2 cathode material has excellent discharge specific capacity and rate and cycle performance. The thermal electrochemical experiments further show that the thermal stability of Li3VO4-coated LiNi0.8Co0.1Mn0.1O2 cathode material in charge-discharge energy storage and conversion system is better than LiNi0.8Co0.1Mn0.1O2 at 30, 40 and 50 °C. The enhanced performance can be attributed to the fact that Li3VO4 coating promotes the transmission of lithium ions and protects the active material from electrolyte corrosion at different temperature, as well as reduces side reaction, electrode polarisation and heat generation of cathode materials. The Li3VO4-coated LiNi0.8Co0.1Mn0.1O2 cathode material has excellent energy storage properties and thermostability, which are beneficial to the development of electronic equipment.